Allopurinol Medication Adherence as a Mediator of Optimal Outcomes in Gout Management. Issue 6 (September 2017) - Coburn, Brian W.; Bendlin, Kayli A.; Sayles, Harlan; Meza, Jane; Russell, Cynthia L.; Mikuls, Ted R.
Abstract : Background: Patient and provider factors, including allopurinol medication adherence, affect gout treatment outcomes. Objectives: The aim of this study was to examine associations of patient and provider factors with optimal gout management. Methods: Linking longitudinal health and pharmacy dispensing records to questionnaire data, we assessed patient and provider factors among 612 patients with gout receiving allopurinol during a recent 1-year period. Associations of patient (medication adherence and patient activation) and provider factors (dose escalation, low-dose initiation, and anti-inflammatory prophylaxis) with serum urate (SU) goal achievement of less than 6.0 mg/dL were examined using multivariable logistic regression. Medication adherence was assessed as a mediator of these factors with goal achievement. Results: A majority of patients (63%) were adherent, whereas a minority received dose escalation (31%). Medication adherence was associated with initiation of daily allopurinol doses of 100 mg/d or less (odds ratio [OR], 1.82; 95% confidence interval [CI], 1.20–2.76). In adjusted models, adherence (OR, 2.35; 95% CI, 1.50–3.68) and dose escalation (OR, 2.48; 95% CI, 2.48–4.25) were strongly associated with SU goal attainment. Low starting allopurinol dose was positively associated with SU goal attainment (OR, 1.11; 95% CI, 1.02–1.20) indirectly through early adherence, but also had a negative direct association with SU goal attainment (OR, 0.21; 95% CI, 0.12–0.37). Conclusions: Medication adherence and low starting dose combined with dose escalation represent promising targets for future gout quality improvement efforts. Low starting dose is associated with better SU goal attainment through increased medication adherence, but may be beneficial only in settings where appropriate dose escalation is implemented. Abstract : Supplemental digital content is available in the text.